Malic acid degradation by indigenous and commercial Saccharomyces cerevisiae wine strains - Pereira, Leonor (2006)
Malic acid contributes to the acidic taste of wine and is, together with tartaric acid, the most abundant organic acid in wine. Contaminating lactic acid bacteria cause wine spoilage after bottling and may use malic acid as a substrate. It is therefore essential to remove excess malic acid from wines to ensure their physical, biochemical and microbial stability. The aim of this work was to gain insight in the differences regarding malic acid metabolism under fermentative conditions among a collection of 294 indigenous Saccharomyces cerevisiae strains selected from the Vinho Verde Region in comparison to commercial wine yeast strains. All strains were screened regarding ethanol tolerance, capacity to utilize acetic and malic acid and acetic acid as well as H2S production. A remarkable heterogeneity of phenotypical traits was found, and only 5 strains (1.7%) of the 294 isolates showed enhanced malic acid degradation using a selective culture medium. The fermentative profiles of 3 strains (318, 319, and 320) in a synthetic must medium were very similar to the ones observed for the commercial strains QA23 and 71B. Considerable differences were also found among these strains regarding the activity of key enzymes involved in the metabolism of malic acid (malic enzyme, malate dehydrogenase, fumarase).